PENGARUH GOOD CORPORATE GOVERNANCE DAN BUSINESS STRATEGY TERHADAP GOING CONCERN PERUSAHAAN - Erliana Banjarnahor; Marieta Ariani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
This study aims to see the influence of corporate governance and business strategy on going concern companies. Sampling method using purposive random sampling that is manufacturing company listed in Bursa Efek Indonesia (BEI) or Indonesia Stock Exchange for the year 2012-2014. The research method used multiple linear regression. Test results shown differentiation strategy has a significant positive effect on Companies’s going concern, while cost strategy and corporate governance have no significant effect on Companies’s going concern. Keywords: Good Corporate Governance, Business Strategy and Company’s Going Concern.